Urbanization processes related to the development of residential functions in gminas adjacent to the city of Olsztyn - Szczepańska, Agnieszka (Bulletin of Geography. Socio-economic Series, 2016)
Political transformations in Poland have led to rapid suburbanization. Suburbias are beginning to develop functions and services characteristic of urban areas. The highest rate of growth is noted in residential development, in particular in the segment of single-family homes. Those developments bring about changes in demographics and social infrastructure. This study analyzes 4,000 real estate transactions conducted in 2007-2014, involving land plots zoned for residential construction, in order to determine the spatial changes that take place in the gminas adjacent to the city of Olsztyn, in view of the development of the local real estate market. The major trends relating to the number of concluded transactions, changes in real estate prices over time, the number of completed construction projects (new single-family homes) and changes in land-use structure are described. Demographic and social changes that inevitably follow from urbanization are described in the analyzed gminas. The results of this study will be used to determine whether Olsztyn's suburbias are merely "bedroom communities" or whether they constitute autonomous territorial units.